Peer Correction Technique in Student Descriptive Text Writing - Helda Oktaviani; Murti Ayu Wijayanti; Akhmad Baihaqi (English Department - Universitas Sultan Ageng Tirtayasa, 2023)
The study aims to determine the implementation of the peer correction technique in students writing descriptive text and how the student's responses to using peer correction technique in students' descriptive text in the tenth grade of SMAN 1 Malingping. The researcher employed a qualitative with a case study. The participants of this research were 33 students of X IPA D in SMAN 1 Malingping. The data were collected from observation, questionnaires, interviews, and documentation. The findings of this research show that the English teacher teaches writing by implementing the peer correction technique. The implementation peer correction technique can stimulate students to be active in-class writing and makes students aware when they make writing mistakes, and peer correction helps them express their ideas without fear of being judged. The peer correction technique gets a positive response from students. Students strongly agreed that the peer correction technique made them critical in their writing